Clinical features of neuroendocrine prostate cancer. (November 2019) - Conteduca, Vincenza; Oromendia, Clara; Eng, Kenneth W.; Bareja, Rohan; Sigouros, Michael; Molina, Ana; Faltas, Bishoy M.; Sboner, Andrea; Mosquera, Juan Miguel; Elemento, Olivier; Nanus, David M.; Tagawa, Scott T.; et al.
Abstract: Background: Neuroendocrine prostate cancer (NEPC) is an aggressive variant of prostate cancer that may arise de novo or in patients previously treated with hormonal therapies for prostate adenocarcinoma as a mechanism of resistance. Despite being important to recognise, the clinical features of NEPC are poorly defined and could help guide when to perform a biopsy to look for NEPC histologic transformation. Methods: We reviewed baseline, treatment and outcome data of 87 patients with metastatic prostate cancer and tumour biopsy confirming NEPC histology. Forty-seven (54.0%) NEPC cases presented de novo, and 40 (46.0%) were therapy-related (t-NEPC). Thirty-six (41.4%) were classified as pure small-cell carcinoma, and 51 (58.6%) demonstrated mixed features with both small-cell carcinoma and adenocarcinoma present. Genomic data were available for 47 patients. Results: The median age at time of NEPC was 68.1 years, median prostate-specific antigen (PSA) was 1.20 ng/ml (0.14 ng/mL small-cell carcinoma, 1.55 ng/mL mixed carcinoma) and sites of metastases included bone (72.6%), lymph node (47.0%), and viscera (65.5%). Median time from adenocarcinoma to t-NEPC diagnosis was 39.7 months (range, 24.5–93.8) with a median of two lines of prior systemic therapy. Platinum chemotherapy was used to treat 57.5% of patients, with a median progression-free survival of 3.9 months. Small-cell carcinoma was associated with worse overall survival (OS) than mixed histology (8.9 months from NEPC diagnosis versus 26.1 months, P < 0.001). Median OS of de novo NEPC was shorter than that of t-NEPC (16.8 months from prostate cancer diagnosis versus 53.5 months, P = 0.043). An average PSA rise per month of ≤0.7 ng/ml before t-NEPC; elevated lactate dehydrogenase levels, RB1 and TP53 loss and liver metastases were poor prognostic features. Conclusions: We describe the clinical features of a cohort of patients with NEPC. These characteristics may inform future diagnostic strategies. Highlights: Neuroendocrine prostate cancer (NEPC) may arise de novo or develop in the later stages of castration-resistant prostate cancer as a mechanism of resistance. NEPC is associated with low PSA and frequent visceral metastases. Small-cell carcinoma is associated with worse overall survival than mixed histology. RB1 and TP53 loss in both de novo and treatment-related NEPC harbours poor outcome.